Jenis Dan Habitat Burung Paruh Bengkok Pada Hutan Wae Illie Taman Nasional Manusela - Lesly Latupapua (Faculty of Agriculture, Pattimura University, 2016)
Manusela National Park has a very high degree of diversity of crooked beak. The objective of this study was to determine the types and habitats of the crooked beak in the Wae Illie forest of Manusela National Park. The method of this research was Ponctualle de'Abondance method. Observation and retrieval of data on birds was done by determining five stations points with 250 m distance between each observation station. The observation time in each station is 20 minutes. Vegetation data has been determined by line plot sampling method for regeneration rate and continuous strip sampling for tree level. The results of the study determined that seven species of parrots, namely Molucas Kakatua (Cacatua moluccensis), red chili pepper (Charmosyna placentis), Nuri Bayan (Eclectus roratus), Nuri Molucas (Eos bornea), Large Coconut Paruh Betet (Tanygnathus megalorynchos) and Perkici rainbow (Trichoglossus haematodus) were accrued points observations. The diversity of bird species is categorized as low;their species diversity H' was 0.3109. Kakatua Seram (Cacatua moluccensis) abundance was 40%, relatively higher that those of other six bird species.